What Are The Most Effective Management Strategies For Nonalcoholic Fatty Liver Disease Across Different Age Groups, Obesity Levels, And Metabolic Risk Profiles? : A Systematic Review - Luthfiyya Syafiqa Tahany; Sinarty Hartanto (International Medical Journal Corp. Ltd, 2025)
Introduction: Nonalcoholic fatty liver disease (NAFLD) is a growing global health issue linked to obesity and metabolic syndrome, ranging from simple steatosis to severe conditions like cirrhosis. Its complex pathophysiology, centered around insulin resistance, necessitates a multifaceted management approach to address its hepatic and extrahepatic consequences. This systematic review synthesizes evidence from recent randomized controlled trials to identify the most effective management strategies across diverse patient populations. Methods: Following PRISMA guidelines, a systematic search was conducted across PubMed, Semantic Scholar, Springer, and Google Scholar. Inclusion criteria targeted randomized controlled trials examining lifestyle, dietary, exercise, or pharmacological interventions for NAFLD, with quantifiable liver and metabolic outcomes. Nine studies were selected for data extraction and quality assessment. Results: The nine trials demonstrated significant improvements with various interventions. Exercise interventions reduced intrahepatic triglycerides by up to 16%. Dietary changes were highly effective; a